2020
DOI: 10.1101/2020.10.24.353789
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Assessing tiger corridor functionality with landscape genetics and modelling across Terai-Arc Landscape, India

Abstract: India led the global tiger conservation initiatives since last decade and has doubled its wild tiger population to 2967 (2603-3346). The survival of these growing populations residing inside the continuously shrinking habitats is a major concern, which can only be tackled through focused landscape-scale conservation planning across five major extant Indian tiger landscapes. The Terai-Arc landscape (TAL) is one of the global priority tiger conservation landscapes holding 22% of the countrys wild tigers. We used… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 55 publications
0
6
0
Order By: Relevance
“…Apart from the diet-based information presented here earlier studies also reported high livestock predation in the fringe areas of Pilibhit TR and Dudhwa NP (Terai habitat) (Basak et al 2016; Chatterjee et al 2017). Such patterns are probably expected as most of these areas are part of tiger source-recipient populations (Corbett, Pilibhit and Dudhwa TR are known sources and Amangarh TR and Terai West FD are recipient populations) (Biswas et al 2020), where dispersing tigers get easy access to livestock/feral cattle (Chatterjee et al 2017; Bargali and Ahmed 2018). One of the interesting pattern observed in this study was similar livestock predation rates (r value=0.4 from ANOSIM analysis) in PAs and non-PAs (7.5% and 12.6% RFOs, respectively), strongly indicating presence of livestock within the PAs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Apart from the diet-based information presented here earlier studies also reported high livestock predation in the fringe areas of Pilibhit TR and Dudhwa NP (Terai habitat) (Basak et al 2016; Chatterjee et al 2017). Such patterns are probably expected as most of these areas are part of tiger source-recipient populations (Corbett, Pilibhit and Dudhwa TR are known sources and Amangarh TR and Terai West FD are recipient populations) (Biswas et al 2020), where dispersing tigers get easy access to livestock/feral cattle (Chatterjee et al 2017; Bargali and Ahmed 2018). One of the interesting pattern observed in this study was similar livestock predation rates (r value=0.4 from ANOSIM analysis) in PAs and non-PAs (7.5% and 12.6% RFOs, respectively), strongly indicating presence of livestock within the PAs.…”
Section: Discussionmentioning
confidence: 99%
“…1, Supplementary data SD1). A total of 1689 large carnivore faecal samples were opportunistically collected (see Supplementary data SD2a) during extensive surveys between November 2014-December 2020 across TAL (Biswas et al 2020). The research team surveyed the animal trails and other habitats and collected these samples in wax-papers, stored in dry boxes until shipped to the laboratory (Biswas et al 2019), where they were finally stored in -20 °C freezer.…”
Section: Sample Collection Species Confirmation and Prey Identificationmentioning
confidence: 99%
“…The park is naturally separated by the river Ganges in two parts, connected by a narrow corridor called as Chilla-Motichur corridor (3 km length and 1 km width) (Johnsingh et al, 1990;Harihar et al, 2018). The eastern part (covering 579 km 2 area of core and buffer zones), situated in the east bank of Ganges maintains structural as well as functional connectivity with major tiger populations (such as Corbett Tiger Reserve) of the landscape (Harihar et al, 2020;Biswas et al 2022a). However, the western part (571 km 2 area on the west bank of Ganges) has become isolated over years from the ERTR.…”
Section: Study Areamentioning
confidence: 99%
“…Some of the major concerns were identification of sampling trails across RTR, seasonal effects, uniform field efforts, constant sampling team etc. As RTR has been a long-term study site for photographic monitoring of tigers (Harihar et al, 2009a;2009b;2012;2020) and earlier genetic studies have used already identified forest trails and tracks (Biswas et al, 2022a), the information was used for faeces collection in this study during both sampling periods (2015 and 2020). Two experienced research and tracking team (each consisting of 3-4 members) surveyed all identified forest trails during 2015 and 2020 and collected fresh faecal samples of large carnivores.…”
Section: Faecal Sampling Species Confirmation and Prey Identificationmentioning
confidence: 99%
“…A significant long-term conservation strategy for endangered carnivores is recognizing and preserving habitat connections that bind source populations to sustain landscape-level gene flow (Yumnam et al, 2014). A major concern is the protection of these increasing populations within the continuously diminishing habitats, which can only be resolved by intensive landscape management planning through five major current Indian tiger landscapes (Biswas et al, 2020).…”
Section: Conservation Strategiesmentioning
confidence: 99%